2009
DOI: 10.1103/physreva.79.023825
|View full text |Cite
|
Sign up to set email alerts
|

Collapses and revivals of stored orbital angular momentum of light in a cold-atom ensemble

Abstract: We report on the storage of orbital angular momentum of light in a cold ensemble of cesium atoms. We employ Bragg diffraction to retrieve the stored optical information impressed into the atomic coherence by the incident light fields. The stored information can be manipulated by an applied magnetic field and we were able to observe collapses and revivals due to the rotation of the stored atomic Zeeman coherence for times longer than 15 µs. PACS numbers: 42.50.Gy, 42.50.Ex, 42.50.Va Light beams carrying orbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 27 publications
(30 reference statements)
1
58
0
2
Order By: Relevance
“…After the seeding work of storing a light-carrying OAM in an atomic ensemble was reported by Moretti et al in Ref. [15], many groups and researchers are active in storing light encoded using a high-dimensional space. Although some work has been reported for light-carrying OAM or spatial structures in different physical systems, such works involve intense light sources [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…After the seeding work of storing a light-carrying OAM in an atomic ensemble was reported by Moretti et al in Ref. [15], many groups and researchers are active in storing light encoded using a high-dimensional space. Although some work has been reported for light-carrying OAM or spatial structures in different physical systems, such works involve intense light sources [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical analysis is based on a previous work [19], which showed that the retrieved field originates from the diffraction of the reading beam into the Zeeman coherence grating and is determined by the optical coherence [10,19], which in the low intensity limit is given by:…”
Section: Theoretical Mode Decompositionmentioning
confidence: 99%
“…Indeed, EIT-based memories have been used to store complex transverse spatial light profiles (images) [12,13], as well as states of orbital angular momentum of light [14,15]. Complex spatial modes and images have also been stored using the GEM technique [16].…”
Section: Introductionmentioning
confidence: 99%